Ecological Assessment and Sustainability of Tea Cultivation in Kangra valley, H.P. - Sankhian, Anurag; Pratap, Dinesh (National Geographical Journal of India, 2022)
Kangra Valley Tea is famous for its unique aroma and quality. Gold and silver medals were awarded at London and Amsterdam in the years 1886 and 1895 for its high quality. Presently, Kangra tea is on the verge of extinction due to various reasons. The study focuses on assessing ecological status and sustainability of the Kangra valley tea cultivation. The main objective of this study was to assess it the main causes for present state of Kangra tea. Results show that the climate of the valley is changing with time but still it is favourable for tea cultivation.